Impact of intentional photo-oxidation of a donor polymer and PC70BM on solar cell performance. Issue 40 (7th October 2019) - Blazinic, Vanja; Ericsson, Leif K. E.; Levine, Igal; Hansson, Rickard; Opitz, Andreas; Moons, Ellen
Abstract : Bond breaking in the PC70 BM cage and gap state formation explain inefficient charge collection upon photooxidation. Abstract : A short lifetime is the main factor hindering the wider implementation of low-cost organic photovoltaics in large-area and outdoor applications. Ingress of oxygen and water vapour through non-ideal encapsulation layers is a known cause of degradation for polymer/fullerene based solar cells. To better understand the origin of this performance degradation, we study the effect of intentional exposure of the photo-active layer to simulated sunlight (AM1.5) in air both on the solar cell performance and on the molecular semiconductor materials. Cathode-free thin films of a blend of the electron donor polymer poly[2, 3-bis-(3-octyloxyphenyl)quinoxaline-5, 8-diyl- alt -thiophene-2, 5-diyl] (TQ1) and the electron acceptor fullerene derivative [6, 6]-phenyl-C70 -butyric acid methyl ester (PC70 BM) were exposed to simulated sunlight in air. Fourier-transform infrared spectra demonstrate the formation of carbonyl photo-oxidation products in the blend films, as well as in the pristine polymer and fullerene films. Solar cells prepared with photo-oxidized active layers show increasingly degraded electrical performance (lower short circuit current, open circuit voltage and fill factor) with increasing exposure time. The increased diode ideality factor indicates that trap-assisted recombination hinders device operation after exposure. The external quantum efficiency decreases drastically with increasing exposure time over the whole photon energy range, while the UV-vis absorption spectra of the blend films only show a mild photo-induced bleaching. This demonstrates that not only the photo-induced degradation of the solar cell performance is not predominantly caused by the loss in light absorption, but charge transport and collection are also hampered. This is explained by the fact that photo-oxidation of PC70 BM causes bonds in its conjugated cage to break, as evidenced by the decreased π* intensity in C1s-NEXAFS spectra of PC70 BM films. This degradation of unoccupied states of PC70 BM will hinder the transport of photo-generated electrons to the electrode. Surface photovoltage spectroscopy gives direct evidence for gap states at the surface of a PC70 BM film, formed after 2 hours of exposure and resulting in upward band bending at the PC70 BM/air surface. These observations indicate that the photo-oxidation of PC70 BM is likely to be the main cause of the performance degradation observed when the photoactive layer of a TQ1:PC70 BM solar cell is intentionally exposed to light in air.